The degradation of ammonia in absorption thermal machines. (September 2017) - Golasi, Iacopo; Salata, Ferdinando; de Lieto Vollaro, Emanuele; Coppi, Massimo
Abstract: When water-ammonia absorption machines are used as heat pumps, the main problems can be found in the components operating at a high pressure (generator-condenser); the increase in temperature with respect to the exertion as refrigerator generates particular conditions that might unbalance the decomposition of ammonia into nitrogen. A decrease in the rate of the refrigerating fluid NH3 in the condenser and evaporator occurs, hence of the performance coefficient of the heat pump with an increased risk of the potential generation of explosive mixtures due to the presence of the hydrogen. The aim of this study is to examine the reaction of ammonia during the dissociation process from a thermodynamic and thermokinetic point of view, focusing on the temperatures and pressures of a heat transformer. With the generator at a temperature of 170 °C it is necessary to reach a degree of dissociation at 1% a time period of the order of 1.013 seconds which is 100 times higher than the one of maximum permanence of the fluid in the components of the machines functioning at high temperatures. This is not a problem that might prevent the realization of high temperature absorption heat pumps.